Founders of the RAS: Henry Thomas Colebrooke. Issue 4 (1st August 2018) - Edmunds, Michael
Abstract : The second President of the RAS was a great scholar, writes Mike Edmunds. Abstract : The second President of the RAS was a great scholar and polymath, but a life spent largely in India was marred by tragedy in later life, writes Mike Edmunds .